AZD8055 enhances in vivo efficacy of afatinib in chordomas. Issue 1 (28th July 2021) - Zhao, Tianna; Siu, I‐Mei; Williamson, Tara; Zhang, Haoyu; Ji, Chenchen; Burger, Peter C; Connis, Nick; Ruzevick, Jacob; Xia, Menghang; Cottone, Lucia; Flanagan, Adrienne M; Hann, Christine L; et al.
Abstract: Chordomas are primary bone tumors that arise in the cranial base, mobile spine, and sacrococcygeal region, affecting patients of all ages. Currently, there are no approved agents for chordoma patients. Here, we evaluated the anti‐tumor efficacy of small molecule inhibitors that target oncogenic pathways in chordoma, as single agents and in combination, to identify novel therapeutic approaches with the greatest translational potential. A panel of small molecule compounds was screened in vivo against patient‐derived xenograft (PDX) models of chordoma, and potentially synergistic combinations were further evaluated using chordoma cell lines and xenograft models. Among the tested agents, inhibitors of EGFR (BIBX 1382, erlotinib, and afatinib), c‐MET (crizotinib), and mTOR (AZD8055) significantly inhibited tumor growth in vivo but did not induce tumor regression. Co‐inhibition of EGFR and c‐MET using erlotinib and crizotinib synergistically reduced cell viability in chordoma cell lines but did not result in enhanced in vivo activity. Co‐inhibition of EGFR and mTOR pathways using afatinib and AZD8055 synergistically reduced cell viability in chordoma cell lines. Importantly, this dual inhibition completely suppressed tumor growth in vivo, showing improved tumor control. Together, these data demonstrate that individual inhibitors of EGFR, c‐MET, and mTOR pathways suppress chordoma growth both in vitro and in vivo . mTOR inhibition increased the efficacy of EGFR inhibition on chordoma growth in several preclinical models. The insights gained from our study potentially provide a novel combination therapeutic strategy for patients with chordoma. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.